Revolutionizing Robotics: Empowering Self-Sustainability with Triboelectric Nanogenerators (International Journal of Food and Nutritional Sciences, 2021)
Triboelectric nanogenerators (TENGs) represent an innovative technology poised to revolutionize the field of self-powered robotic systems. These devices can efficiently convert mechanical energy into electrical energy, eliminating the need for external power sources and offering exceptional actuation, grasping, and sensing capabilities. This comprehensive review explores the extensive potential of TENG mechanisms and modes in various robotic applications. Initially, we investigate the enhanced efficiency and reliability of TENG-based actuation systems, highlighting their inherent self-powering capabilities. Subsequently, we focus on TENG-driven grippers, equipped with precise gripping capabilities and the unique ability to self-calibrate, enabling agile and accurate object manipulation.